2011
DOI: 10.1128/jvi.01998-10
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Mediates the Antiviral Effect of Gamma Interferon against Hepatitis B Virus in Human Hepatocyte-Derived Cells

Abstract: Alpha interferon (IFN-␣) is an approved medication for chronic hepatitis B. Gamma interferon (IFN-␥) is a key mediator of host innate and adaptive antiviral immunity against hepatitis B virus (HBV) infection in vivo.In an effort to elucidate the antiviral mechanism of these cytokines, 37 IFN-stimulated genes (ISGs), which are highly inducible in hepatocytes, were tested for their ability to inhibit HBV replication upon overexpression in human hepatoma cells. One ISG candidate, indoleamine 2,3-dioxygenase (IDO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 69 publications
10
110
0
1
Order By: Relevance
“…The expression of IDO by costimulatory DCs is further reinforced under conditions of immune activation, after reverse signaling by T cells through GITR ligand or CD80/CD86 or stimulation by IFN-g or TLR ligands. Recruitment of IDO + macrophages, B cells, and stromal cells also occurs through this mechanism (16,17).…”
Section: Endritic Cells (Dcs) Comprise a Heterogeneous Group Ofmentioning
confidence: 99%
“…The expression of IDO by costimulatory DCs is further reinforced under conditions of immune activation, after reverse signaling by T cells through GITR ligand or CD80/CD86 or stimulation by IFN-g or TLR ligands. Recruitment of IDO + macrophages, B cells, and stromal cells also occurs through this mechanism (16,17).…”
Section: Endritic Cells (Dcs) Comprise a Heterogeneous Group Ofmentioning
confidence: 99%
“…We found that miR-122 acts as an HBV suppressor miRNA, indicating that IFN-␣-induced miR-122 inhibition may attenuate the anti-HBV activity of IFN-␣. IFN-␣ is capable of inducing hundreds of genes (ISGs), and their antiviral effects have been studied extensively (8,9,(48)(49)(50). However, the exact role of each ISG still remains unclear, and even controversial (15,51).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown that besides a stimulating effect on cytotoxic T lymphocytes and natural killer cell function, IFN-based therapy (IFN-␣-2b and pegylated IFN-␣-2a or -2b) also has a direct antiviral effect by preventing the formation or accelerating decay of viral capsids and/or inducing antiviral ISGs that inhibit HBV expression and replication (8)(9)(10)(11)(12)(13). Inhibition of IFN-␣ signaling by HBV has been suggested to antagonize the IFN response (14).…”
mentioning
confidence: 99%
“…Indeed, the secretome of ADSCs has been shown to possess the capability of immunomodulation [19]. It is well known that IL-6, IDO, IFNγ and TNF-α are modulators of the hepatocyte immune response and regeneration [20][21][22][23]. We examined production of the four cytokines in the supernatant and found a high level of IL-6 in the coculture medium, while in the rat hepatocyte monoculture, IL-6 concentration was too low to be measured by ELISA.…”
Section: Discussionmentioning
confidence: 99%